Role of T lymphocytes in rat 2, 4, 6-trinitrobenzene sulphonic acid (TNBS) induced colitis: increased mortality after γδ T cell depletion and no effect of αβ T cell depletion. Issue 4 (1st April 2001) - Hoffmann, J C; Peters, K; Henschke, S; Herrmann, B; Pfister, K; Westermann, J; Zeitz, M
Abstract : BACKGROUND AND AIM: Indirect evidence suggests that CD4 + T cells have a pathogenic while γδ T cells have a protective role in the initiation and perpetuation of inflammatory bowel disease. To define the role of T cell subsets in a rat colitis model (2, 4, 6-trinitrobenzene sulphonic acid (TNBS)) we analysed colitis severity after effective depletion of T helper cells, αβ Τ cells, or γδ T cells. METHODS: T helper cells, αβ T cells, or γδ T cells were depleted using previously described monoclonal antibodies directed at the CD4 molecule (OX38), the CD2 molecule (OX34, both depleting CD4 + T cells), the αβ T cell receptor (R73), and the γδ T cell receptor (V65). Depletion was verified by flow cytometry and/or immunohistology. Colitis was induced using intracolonic application of TNBS. RESULTS: Surprisingly, depletion of T helper cells or αβ T cells had no influence on survival, macroscopic or microscopic scores, or myeloperoxidase activity following colitis induction. In contrast, depletion of γδ T cells resulted in significantly increased mortality (V65: 73%, n=15) compared with controls (30%, n=13; p<0.03). In addition, colitis was histologically more severe in the γδ T cell depleted group compared with controls (p<0.05). CONCLUSIONS: T helper cells or αβ T cells did not influence the initiation or perpetuation of rat TNBS colitis. In contrast, γδ T cells had a protective role in rat TNBS colitis as depletion caused increased mortality.